Iot based dust alerting and smartbin system for asthma patient - Periasamy, Innarasi; Ramalingam, Mritha (2021)
Invent an idea to develop an internet of thing (iot) based dust alerting and smartbin system for asthma patients.the kit detects the dust and measure the rubbish level in asthma patient ward and then send the notification to the cleaner of the ward to clean.